2017
DOI: 10.1038/s41598-017-06642-w
|View full text |Cite
|
Sign up to set email alerts
|

Glargine and degludec: Solution behaviour of higher dose synthetic insulins

Abstract: Single, double and triple doses of the synthetic insulins glargine and degludec currently used in patient therapy are characterised using macromolecular hydrodynamic techniques (dynamic light scattering and analytical ultracentrifugation) in an attempt to provide the basis for improved personalised insulin profiling in patients with diabetes. Using dynamic light scattering and sedimentation velocity in the analytical ultracentrifuge glargine was shown to be primarily dimeric under solvent conditions used in cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
3
6
0
Order By: Relevance
“…It is interesting to note that the study of insulins glargine and detemir using AUC (either SV or SE) have been limited or non-existent. IGla was reported by our group [ 3 ] as part of a dosage study involving the single and triple dose forms and similar results are observed in this present investigation. IDet showed interesting multi-hexameric behaviour in AUC-SV, but this was not present in AUC-SE; possibly due to the very high concentration involved (and therefore high signal from the main peak) as well as the low-resolving power from SE analysis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is interesting to note that the study of insulins glargine and detemir using AUC (either SV or SE) have been limited or non-existent. IGla was reported by our group [ 3 ] as part of a dosage study involving the single and triple dose forms and similar results are observed in this present investigation. IDet showed interesting multi-hexameric behaviour in AUC-SV, but this was not present in AUC-SE; possibly due to the very high concentration involved (and therefore high signal from the main peak) as well as the low-resolving power from SE analysis.…”
Section: Discussionsupporting
confidence: 92%
“…Although we did not find similar multi-hexameric behaviour in IDeg, we did observe dihexamers. In addition, we found a high degree of non-ideality, confirmed from a previous investigation [ 3 ] to be a result of a lack of buffering salts in the drug preparation. It is possible that the excipient composition in the product prevents the formation of these fibres.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…PSD for IDeg at 4 • C was approximately 4 nm, which is in agreement with previous studies [38,39]. On Day 1, significant changes were observed in IDeg when it was subjected to increasing temperature (F 1,2 = 375.01, p = 0.03).…”
Section: Particle Size Distributionsupporting
confidence: 91%
“…The solution structure of degludec has been studied by both small-angle X-ray scattering (SAXS; Steensgaard et al, 2013) and analytical ultracentrifugation (Adams et al, 2017(Adams et al, , 2018Steensgaard et al, 2013). While there is general agreement that degludec is found as a dihexamer in phenol-containing solutions, different crystal forms show ambiguous intermolecular contacts (Steensgaard et al, 2013).…”
Section: Introductionmentioning
confidence: 99%